Phase transitions of caesium nitrate embedded in nanoporous alumina films - Pavlov Aleksei; Stukova Elena; Baryshnikov Sergey (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2023)
In order to make material with improved properties, nanocomposites based on nanoporous Al2O3 films (having different pore sizes) filled with ferroelectric, namely, caesium nitrate CsNO3, have been fabricated, and their electrophysical charactistics have been investigated. The film surfaces were tested by electron microscopy. Temperature dependences of the effective permittivity ε' and of the third harmonic coefficient were measured for the nanocomposites. The phase-transition points were determined by the maximum value of the dε'/dT derivative. The reduction in pore was found to lead to a decrease in the Curie temperature (by more than 30 K) and a phase transition blur. This phenomenon is associated with the influence of intrinsic size effects.